Sweating the Assets: Asset Leanness and Financial Performance in the Motor Carrier Industry. Issue 1 (March 2016) - Fawcett, Amydee M.; Jin, Yao Henry; Hofer, Christian; Waller, Matthew A.; Brazhkin, Vitaly
Abstract : Originally adopted by the automotive manufacturers, lean management practices have since been applied to many other manufacturing industries. This study reviews the different theoretical perspectives on the leanness‐performance relationship in the context of the motor carriage industry. Drawing on both the lean management in logistics and organizational slack literatures, we develop hypotheses addressing the link between asset leanness and financial performance. These hypotheses are empirically tested using a comprehensive panel data set of 1, 172 firm‐quarter observations from the U.S. publicly traded truckload motor carriers. Initially expecting an inverted U‐shaped relationship between asset leanness and performance, findings indicated a U‐shaped relationship, both for carriers' total assets and the subset of trailer assets.